التوجه الإصلاحي في النضال الصحفي لعبد العزيز الثعالبي وإبراهيم بن الحاج عيسى أبو اليقظان - لمجد, شهرزاد (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة إلى إبراز الاهتمام المبكر لرجلي الإصلاح التونسي(من أصول جزائرية) عبد العزيز الثعالبي والجزائري إبراهيم بن الحاج عيسى أبو اليقظان بالممارسة الصحفية، وحرصهما على استثمار وتوظيف الصحافة كوسيلة لبلورة الوعي وتشكيل الرأي العام نحو قضايا اشتغالهما بما يخدم توجههما الإصلاحي مع التركز تحديدا على محاربتهما الجمود الفكري وحثهما على التجديد الديني وفتح مجالي البحث والاجتهاد والأخذ بأسباب العلم والتربية وإصلاح مناهج وأساليب التعليم، وهي عوامل اقتنع الرجلان بضرورتها لتحقيق نهضة المجتمعات العربية والإسلامية. كما تهدف الدراسة إلى تحديد إطار العلاقة الخاصة التي جمعت بين المصلحين وسياق لقائهما بتونس ونضالهما المشترك ضمن تيار الحركة الإصلاحية الذي ولد في ظروف تاريخية استثنائية كانت البلدان العربية والإسلامية تشهد فيها حالة من التدهور والتراجع الحضاريين وتتعرض إلى هجمة استعمارية شرسة. This study aims to highlight the early interest of both reformers: Tunisian (from Algerian roots) Abdul Aziz Al-Thaalibi and Algerian Ibrahim Ben Al -Hadj Aissa Abu Al-yakdan in journalistic practice .Both reformers cared about investing and employing the press as a mean of developing awareness and shaping public opinion towards the issues that serve their reformist orientation. with a focus specifically on Fighting intellectual stagnation, urging religious renewal, opening the fields of research and ijtihad, adopting the science and education approach, and reforming educational curricula and methods These factors were considered by both men to be essential for the renaissance of Arab and Islamic societies. The study also aims to define the framework of the special relationship between the reformers and the context of their meeting with Tunisia and their common activism within the mainstream of the reformist movement. This movement was born in exceptional historical circumstances when the Arab and Islamic countries were experiencing a state of decline and decline in civilization and were subjected to a vicious colonial onslaught.
مقال
Keywords: عبد العزيز الثعالبي؛ أبو اليقظان؛ الإصلاح؛ التجديد الديني؛ التعليم; Abdul Aziz Al–Thaalibi; Abu Al-Yakdan; Reform; Religious Renewal; Education